Combination effect of voluntary exercise and garlic (Allium sativum) on oxidative stress, cholesterol level and histopathology of heart tissue in type 1 diabetic rats - Rafighe Ghyasi; Gisou Mohaddes; Roya Naderi (Journal of Cardiovascular and Thoracic Research, 2019)
Introduction: This study aimed to evaluate the combination effect of voluntary exercise and garlic on oxidative markers, cholesterol level and histological alterations in streptozotocin (STZ)- induced diabetes in rat heart. Methods: Thirty-five male Wistar rats were randomly assigned into five experimental groups (n=7): Control, Diabetes, Diabetes+Garlic, Diabetes+Exercise, Diabetes+Garlic+Exercise groups. Diabetes was induced by STZ (ip, 50 mg/kg) in animals. Animals received garlic homogenate (250 mg/kg) by oral gavage or subjected to voluntary exercise alone or together for 6 weeks. At the end of intervention blood and heart tissue samples were obtained and used for measurement of glycosylated haemoglobin (HbA1c), cholesterol, total antioxidant capacity (TAC), malondialdehyde (MDA) levels and histological analysis. Results: Improved blood glucose, cholesterol, total antioxidant capacity, and MDA levels were established in both Diabetes+Garlic and Diabetes+Exercise groups. Additionally, staining with Hematoxylin and Eosin (H&E) revealed that voluntary exercise and garlic alone and together reduced interstitial edema, leukocyte infiltration, and myonecrosis. Furthermore, simultaneous treatment of diabetic rats with garlic and exercise training had an additive effect on these parameters. Conclusion: The findings indicated that combination therapy with garlic and voluntary exercise may present more beneficial effects in heart histological remodeling in diabetic rats than the use of garlic or voluntary exercise alone and that these beneficial effects might be associated with enhancement in cholesterol, total antioxidant capacity, and MDA levels.